PENDAMPINGAN TEKNIK MENDONGENG SEBAGAI METODE PENGAJARAN ORANG TUA DI LINGKUNGAN MASYARAKAT CIDAWANG - Herni Fitriani; Puji Adi Pertiwi; Dedi Febriyanto (JOURNAL OF COMMUNITY DEDICATION, 2023)
Fairy tales are stories that do not really happen or are stories created by the author's imagination. One of the intrinsic elements in fairy tales is that they have a message or moral message. Therefore, fairy tales can be used as a medium to shape children's character because they have moral values that children can learn. The strategy for building children's character is carried out by providing examples, getting used to reading fairy tales, getting used to listening to fairy tales, and creating a supportive reading environment. Accompanying this storytelling technique is also a literacy activity as a form of oral tradition that needs to be maintained. Storytelling is an activity to train language skills as a supporting factor in children. Storytelling is also an activity that approaches parents and children, one of which is as a supporting factor for cognitive development so that children can be interested in reading and listening to fairy tales and are not dependent on gadgets. The aim of this service is to apply fairy tale-based learning to shape children's character in the millennium era optimally, be fun, and be integrated with family and school as well as provide parents with awareness that storytelling activities can release children from their dependence on gadgets, as well as provide various positive stimuli to children. This service uses parental teaching methods. The results achieved were that there was a high desire among parents to return to the old tradition, namely storytelling with material that is appropriate for today. Participants appreciated the event, understood the role of fairy tales as forming children's characters so they were interested in carrying them out.